Lamin A/C Mechanosensor Drives Tumor Cell Aggressiveness and Adhesion on Substrates With Tissue-Specific Elasticity - Urciuoli, Enrica; D’Oria, Valentina; Petrini, Stefania; Peruzzi, Barbara (Frontiers in Cell and Developmental Biology, 2021)
Besides its structural properties in the nucleoskeleton, Lamin A/C is a mechanosensor protein involved in perceiving the elasticity of the extracellular matrix. In this study we provide evidence about Lamin A/C-mediated regulation of osteosarcoma cell adhesion and spreading on substrates with tissue-specific elasticity. Our working hypothesis is based on the observation that low-aggressive and bone-resident SaOS-2 osteosarcoma cells express high level of Lamin A/C in comparison to highly metastatic, preferentially to the lung, osteosarcoma 143B cells, thereby suggesting a role for Lamin A/C in tumor cell tropism. Specifically, LMN-A gene over-expression in 143B cells induced a reduction in tumor cell aggressiveness in comparison to parental cells, with decreased proliferation rate and reduced migration capability. Furthermore, LMN-A reintegration into 143B cells changed the adhesion properties of tumor cells, from a preferential tropism towards the 1.5 kPa PDMS substrate (resembling normal lung parenchyma) to the 28 kPa (resembling pre-mineralized bone osteoid matrix). Our study suggests that Lamin A/C expression could be involved in the organ tropism of tumor cells, thereby providing a rationale for further studies focused on the definition of cancer mechanism of metastatization.